Algoritmo e implementación del análisis factorial de correspondencias - Castillo Elizondo, William (1997)
In this article, it is presented an algorithm in pseudo-code for the Factor Analysis of Correspondence. Some comments on the implementationn on C++ are also developed. Finally, the method is illustrated by an example.